2023
DOI: 10.1186/s41182-023-00550-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of wild edible and nutraceutical plants in Raya-Azebo District of Tigray Region, northern Ethiopia

Mirutse Giday,
Tilahun Teklehaymanot

Abstract: Background Although there is a wide use of wild edible plants (WEPs) in Ethiopia, very little work has so far been done, particularly, in the Tigray Region, northern Ethiopia, to properly document the associated knowledge. The purpose of this study was, therefore, to document knowledge and analyze data related to the use of wild edible and nutraceutical plants in Raya-Azebo District of Tigray Region. The district was prioritized for the study to avoid the further loss of local knowledge and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
0
8
1
Order By: Relevance
“…This finding revealed that WEPs were mainly collected in the January, May, February, and December months and relatively rare in September and October. Contrary to the current study, the study conducted by [ 23 ] in Raya-Azebo district, northern Ethiopia, described September and October as the main harvesting months for wild edible plants. In another study [ 9 ], March, April, and May months were reported as the major harvesting periods in Mieso district, eastern Ethiopia.…”
Section: Resultscontrasting
confidence: 65%
See 3 more Smart Citations
“…This finding revealed that WEPs were mainly collected in the January, May, February, and December months and relatively rare in September and October. Contrary to the current study, the study conducted by [ 23 ] in Raya-Azebo district, northern Ethiopia, described September and October as the main harvesting months for wild edible plants. In another study [ 9 ], March, April, and May months were reported as the major harvesting periods in Mieso district, eastern Ethiopia.…”
Section: Resultscontrasting
confidence: 65%
“…Rich Dhoqunu gurracha (AO) Malvaceae Sh F Fr U Rv,Fm [ 9 , 12 , 15 , 17 , 21 , 24 , 25 ] BA-102 Grewia mollis Juss. * Qoriya (Shi) Malvaceae T B,F Fr,Ck Bf,M,U,Lu,Ts Ow,Rv [ 11 , 14 , 23 , 32 , 34 , 36 ] BA-35 Justicia schimperiana (Hochst. ex Nees) T. Anderson.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was noted in most of these correspondences that the nutritional value of foods made from unusual plants may occasionally be better than that of ordinary vegetables. Therefore, the creation of a national food composition database is urged globally [ 9 ]. Furthermore, nutritional data are needed to create processing parameters for the target items that are appropriate for low-income consumers [ 10 ].…”
Section: Introductionmentioning
confidence: 99%